Microbiota Analysis of Chickens Raised Under Stressed Conditions - Mandal, Rabindra K.; Jiang, Tieshan; Wideman, Robert F.; Lohrmann, Troy; Kwon, Young Min (Frontiers in Veterinary Science, 2020)
A substantial progress has been made towards understanding stress-associated gut and extraintestinal microbiota. However, a comprehensive understanding of the extraintestinal microbiota of chickens raised under stress condition is lacking. In this study, chickens were raised on wire floor model to induce stress, and the microbiotas in the gut (ceca) and extraintestinal sites (blood, femur, and tibia) were characterized at different ages (1, 17, and 56 days) using 16S rRNA gene microbiota profiling. Open reference OTU picking showed extraintestinal sites had a significantly higher number of unassigned OTUs compared to ceca across all ages of chickens. Extraintestinal sites of all ages, irrespective of body sites, as well as ceca of one day old chickens had significantly lower alpha diversity than ceca of older chickens. Intriguingly, bacterial diversity (alpha and beta) and OTU interaction network analysis showed relatively stable bacterial composition within the extraintestinal sites of chickens regardless of age and sites compared to ceca. Furthermore, assessment using UniFrac distance suggested the gut as a possible source of extraintestinal bacteria. Lastly, LEfSe analysis showed that both commensal and pathogenic bacteria were translocated into the extraintestinal tissues and organs under the stress. Extraintestinal sites have highly abundant novel taxa that need to be further explored. In ovo microbiota colonization and/or translocation of circulating maternal blood microbiota into ovarian follicles might be the source of intestinal and extraintestinal microbiota in one day old chickens. Our comprehensive microbiota data including extraintestinal sites in reference to gut provides unique insights into microbiota of chickens raised under stress condition, which may be relevant in other animal species as well.